Autophagy Regulates Programmed Cell Death during the Plant Innate Immune Response - Liu, Y.; Schiff, M.; Czymmek, K.; Tallóczy, Z.; Levine, B.; Dinesh-Kumar, S.P.
The plant innate immune response includes the hypersensitive response (HR), a form of programmed cell death (PCD). PCD must be restricted to infection sites to prevent the HR from playing a pathologic rather than protective role. Here we show that plant BECLIN 1, an ortholog of the yeast and mammalian autophagy gene ATG6/VPS30/beclin 1, functions to restrict HR PCD to infection sites. Initiation of HR PCD is normal in BECLIN 1-deficient plants, but remarkably, healthy uninfected tissue adjacent to HR lesions and leaves distal to the inoculated leaf undergo unrestricted PCD. In the HR PCD response, autophagy is induced in both pathogen-infected cells and distal uninfected cells; this is reduced in BECLIN 1-deficient plants. The restriction of HR PCD also requires orthologs of other autophagy-related genes including PI3K/VPS34, ATG3, and ATG7. Thus, the evolutionarily conserved autophagy pathway plays an essential role in plant innate immunity and negatively regulates PCD.